Association of birth defects during the perinatal period with child mortality under 5 years - Xie, Donghua; Wei, Jianhui; Xiong, Lili; Zhu, Huiyuan; Peng, Xianglian; Li, Bo; Zou, Kehan (Frontiers in Pediatrics, 2025)
ObjectiveTo calculate the impact of birth defects (BDs) diagnosed during the perinatal period on the mortality of children under 5 years of age.MethodsThis was a retrospective cohort analysis. From the monitoring system, we collected all hospital delivery, BD monitoring, and death information for children under 5 years in Hunan Province from 2017–2022. These data were linked by ID number. Mortality rates and Cox proportional hazards models were used to compute hazard ratios (HRs) and 95% confidence intervals (CIs) for the impact of BDs on mortality in children under 5 years of age.ResultsAmong 3,807,340 live-born children, 29,879 (0.8%) had at least one type of BDs during the perinatal period, with a total of 12,215,033 person-years of follow-up. The mortality rate of the BDs group was 14.5% (95% CI: 13.7–15.3) per 1,000 person-years, which was 11.6 times (HR = 11.6, 95% CI: 10.5–12.8) greater than that of the nondefect group. The mortality rate per 1,000 person-years of girls with BDs was higher than that of boys (15.4% vs. 13.5%). For the BDs group, congenital anomalies (CAs) were the most common cause of death (57.2%). Compared with children without BDs, those with BDs had elevated mortality risks for CAs (HR, 58.1; 95% CI, 42.7–79.0), digestive (HR = 16.5, 95% CI: 6.1–45.0) and respiratory system malformations (HR, 11.9; 95% CI, 7.9–17.8), and cancer (HR = 11.1 95% CI: 4.7–26.2).ConclusionsThis study revealed that BDs were strongly associated with mortality under 5 years of age, especially in the first 28 days, for muscular, chromosomal, genetic, and nervous system abnormalities.